123k views
2 votes
Find a general solution of
t *(dy/dt)-(y^2)*lnt+y=0

User Tlastowka
by
5.2k points

1 Answer

3 votes


t(\mathrm dy)/(\mathrm dt)-y^2\ln t+y=0

Divide both sides by
y(t)^2:


ty^(-2)(\mathrm dy)/(\mathrm dt)-\ln t+y^(-1)=0

Substitute
v(t)=y(t)^(-1), so that
(\mathrm dv)/(\mathrm dt)=-y(t)^(-2)(\mathrm dy)/(\mathrm dt).


-t(\mathrm dv)/(\mathrm dt)-\ln t+v=0


t(\mathrm dv)/(\mathrm dt)-v=\ln t

Divide both sides by
t^2:


\frac1t(\mathrm dv)/(\mathrm dt)-\frac1{t^2}v=(\ln t)/(t^2)

The left side can be condensed as the derivative of a product:


(\mathrm d)/(\mathrm dt)\left[\frac1tv\right]=(\ln t)/(t^2)

Integrate both sides. The integral on the right side can be done by parts.


\displaystyle\int(\ln t)/(t^2)\,\mathrm dt=-\frac{\ln t}t+\int(\mathrm dt)/(t^2)=-\frac{\ln t}t-\frac1t+C


\frac1tv=-\frac{\ln t}t-\frac1t+C


v=-\ln t-1+Ct

Now solve for
y(t).


y^(-1)=-\ln t-1+Ct


\boxed{y(t)=\frac1{Ct-\ln t-1}}

User Sumchans
by
5.3k points